Phenotypic Detection of Carbapenemases in Klebsiella Pneumoniae from Clinical Isolates in a Tertiary Care Hospital - Dr. S. Rajeswari,; Dr. M. Umamaheswari,; Dr. R.Vasanthi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: The rise in carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a serious therapeutic challenge, especially in resource-limited settings. Phenotypic tests serve as essential diagnostic tools for detecting carbapenemase production. Aim: To evaluate and compare the efficacy of three phenotypic methods—Modified Hodge Test (MHT), Combined Disc Test (CDT), and Rapidec Carba NP (RCNP)—in detecting carbapenemase production among K. pneumoniae isolates. Methods: In a prospective study from September 2016 to August 2017, a total of 196 non-repetitive clinical isolates of K. pneumoniae were collected from a tertiary care hospital. Isolates were tested for meropenem resistance using E-test, followed by phenotypic detection using MHT, CDT, and RCNP. Results: Out of 196 isolates, 26 (13.27%) were resistant to meropenem (MIC ≥4 µg/ml). Among these 26, 16 (61.5%) were positive by MHT, 22 (84.6%) were MBL-positive by CDT, and 21 (80.8%) were positive by RCNP. Conclusion: Among the three methods, the Combined Disc Test showed the highest detection rate, followed by RCNP. The MHT demonstrated relatively lower sensitivity. Phenotypic methods continue to be valuable diagnostic tools in settings where molecular diagnostics are unavailable.